Implementasi Integrated Marketing Communication Untuk Meningkatkan Kinerja Penjualan Di PT. Pro-Specs Indopratama - Azirial Haykel Ab Aziz (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to analyze the Integrated Marketing Communication (IMC) strategy implemented by PT. Pro-Specs Indopratama (PSI) in an effort to expand brand awareness, retain customers and expand market share in the Non-Destructive Testing (NDT) industry in the Asia Pacific region. We collected data through interviews with 10 internal staff involved in implementing IMC. The analysis results show that PSI uses various media, such as websites, social media, email, and industry events, to reach target audiences. They have an active strategy of attending industry exhibitions and conducting NDT equipment demonstrations. PSI's marketing communications objectives are to increase brand awareness, expand market share, and retain existing customers. Employees play an important role in the implementation of IMC strategy by becoming company brand ambassadors. Coordination between departments involved in IMC is carried out through regular meetings.